Understanding Stress, Job Satisfaction and Physical Well Being Job - Ridha Rahma Nisa; Izdiharunnisa Izdiharunnisa; Ramot Hasugian; Muhammad Nur Habibie; Diana Stevani Br Tarigan (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study is to identify models for sources of stress, satisfaction and physical well-being and the relationship between the three. A total of 338 private sector managers from the Klang Valley provided a self-monitoring report. The results obtained show that the structural modeling does not change the fit index, a source of stress which includes workload, acceptance, and the balance between relationships and homework. In addition, stress sources are negatively related to satisfaction and physical well-being, satisfaction is a mediator for stress sources and physical well-being. Stress affects the physical well-being of managers through satisfaction.